BRAF and NRAS mutated melanoma: Different Ca2+ responses, Na+/Ca2+ exchanger expression, and sensitivity to inhibitors. (September 2020) - Esteves, Gabriela Nohemi Nuñez; Ferraz, Letícia Silva; Alvarez, Marcela Maciel Palacio; Costa, Claudia Alves da; Lopes, Rayssa de Mello; Tersariol, Ivarne Luis dos Santos; Rodrigues, Tiago
Graphical abstract: Highlights: SK-MEL-19 (BRAF V600E -mutated) and SK-MEL-147 (NRAS Q61R -mutated) human melanoma cells exhibit differences in Ca 2+ homeostasis. NRAS Q61R mutated melanoma was more sensitive to Ca 2+ withdraw than the BRAF V600E mutated cells. Thapsigargin elicits a higher cytosolic Ca 2+ increase in in BRAF V600E mutated than in NRAS Q61R mutated melanoma cells. NRAS Q61R mutated melanoma exhibited higher expression of NCX1 and was more susceptible to NCX inhibition than BRAF V600E mutated. Combined therapy with B-RAF and NCX inhibitors may potentially represent a new therapeutic strategy to the treatment of melanomas. Abstract: Calcium is a ubiquitous intracellular second messenger, playing central roles in the regulation of several biological processes. Alterations in Ca 2+ homeostasis and signaling are an important feature of tumor cells to acquire proliferative and survival advantages, which include structural and functional changes in storage capacity, channels, and pumps. Here, we investigated the differences in Ca 2+ homeostasis in vemurafenib-responsive and non-responsive melanoma cells. Also, the expression of the Na + /Ca 2+ exchanger (NCX) and the impact of its inhibition were studied. For this, it was used B-RAF V600E and NRAS Q61R -mutated human melanoma cells. The intracellular Ca 2+ chelator BAPTA-AM decreased the viability of SK-MEL-147 but not of SK-MEL-19 and EGTA sensitized NRAS Q61R -mutated cells to vemurafenib. These cells also presented a smaller response to thapsargin and ionomycin regarding the cytosolic Ca 2+ levels in relation to SK-MEL-19, which was associated to an increased expression of NCX1, NO basal levels, and sensitivity to NCX inhibitors. These data highlight the differences between B-RAF V600E and NRAS Q61R -mutated melanoma cells in response to Ca 2+ stimuli and point to the potential combination of clinically used chemotherapeutic drugs, including vemurafenib, with NCX inhibitors as a new therapeutic strategy to the treatment of melanoma.